2012
DOI: 10.1128/jcm.02083-12
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Clinical Evaluation of the Portrait Toxigenic C. difficile Assay for Detection of Toxigenic Clostridium difficile Strains in Clinical Stool Specimens

Abstract: f We compared the Portrait Toxigenic C. difficile Assay, a new semiautomated sample-to-result molecular test, to a toxigenic bacterial culture/cell cytotoxin neutralization assay (TBC/CCNA) for the detection of toxigenic Clostridium difficile in 549 stool specimens. Stool specimens were also tested by one of three alternative FDA-cleared molecular tests for toxigenic C. difficile (Xpert C. difficile, Illumigene C. difficile, or GeneOhm Cdiff). The sensitivities and specificities of the molecular tests compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…Assay characteristics did not, however, differ significantly. The data for the BD MAX Cdiff assay were comparable to those from a previous study (7), and both molecular assays confirmed the high sensitivity and specificity rates of C. difficile PCR assays (3,5,(14)(15)(16)(17)(18). Also, no differences were observed when the Xpert C. difficile and the BD GeneOhm Cdiff assays were compared (19); thus, equal performance of all three assays can be assumed.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Assay characteristics did not, however, differ significantly. The data for the BD MAX Cdiff assay were comparable to those from a previous study (7), and both molecular assays confirmed the high sensitivity and specificity rates of C. difficile PCR assays (3,5,(14)(15)(16)(17)(18). Also, no differences were observed when the Xpert C. difficile and the BD GeneOhm Cdiff assays were compared (19); thus, equal performance of all three assays can be assumed.…”
supporting
confidence: 73%
“…Five patients received a relevant antibiotic treatment that might explain false-positive PCR detection of DNA from dead bacteria. However, 3 patients provided other samples that were culture positive, arguing that molecular detection was truly more sensitive (14,21). Seven true-positive samples were missed by the BD MAX Cdiff assay; of those, 6 were positive by the Xpert assay.…”
mentioning
confidence: 99%
“…After reviewing the titles and abstracts, 21 articles were selected for full-text evaluation (Figure 1). Sixteen articles with 18 studies published between 2005 and 2014 reported the sensitivity and specificity of LAMP on stool samples for the diagnosis of C. difficile infection, and were included in our meta-analysis [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Five articles were excluded (reasons for exclusion in Figure 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…It would take only a few additional false results to make the platform appear less sensitive or specific. Despite the fact that there are some significant differences between platforms, the results with all platforms compare favorably to those obtained with other molecular assays for the detection of C. difficile, as evidenced by the product inserts and many additional clinical studies (11,(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 52%
“…These assays can be performed within a few hours, but they lack sensitivity and specificity, and the GDH assays cannot differentiate between cytotoxic and noncytotoxic strains of C. difficile. EIAs are not recommended as the sole diagnostic for detection of C. difficile disease (1,(7)(8)(9)(10)(11). Cell culture cytotoxicity neutralization assays (CCNA) detect the presence of C. difficile cytotoxin by inoculating cell cultures with clarified stool specimens in the presence and absence of C. difficile antitoxins and can take up to 48 h to complete.…”
mentioning
confidence: 99%